NICKNAMES AS A REFLECTION OF WORLD PERCEPTION: LINGUOCULTURAL PERSPECTIVE (TAMADDUN NURI JURNALI, 2025)
The article examines nicknames as an important element of the linguistic and cultural worldview. Nicknames are analyzed in terms of their semantics, pragmatics, and cultural conditioning. Similarities and differences in the functioning of nicknames in the Russian and English languages are identified, and their role in reflecting folk classification, values, and social order is emphasized.